Examining the effect of improved context sensitive morphology on Arabic information retrieval - Darwish, Kareem; Hassan Awadalla, Hany; Emam, Ossama (ACL Workshop on Computational Approaches to Semitic Languages, 2005)
This paper explores the effect of improved morphological analysis, particularly context sensitive morphology, on monolingual Arabic Information Retrieval (IR). It also compares the effect of context sensitive morphology to non-context sensitive morphology. The results show that better coverage and improved correctness have a dramatic effect on IR effectiveness and that context sensitive morphology further improves retrieval effectiveness, but the improvement is not statistically significant. Furthermore, the improvement obtained by the use of context sensitive morphology over the use of light stemming was not significantly significant.